Advanced statistical techniques of direct marketing tests - Leventhal, Barry (Henry Stewart Talks, 2008)
Objectives of the talk, Terms and definitions used in statistical experiments, Single factor experiments, Model description, Fixed vs random models, Analysis of variance rationale (ANOVA), Example: experiment on recruitment channels, Randomised blocks and latin squares, Factorial experiments, Analysis of experiments, Example, Summary of main points